From Cantor To Christaller? - Morris, E Scott (Quaestiones Geographicae, 2015)
It is possible that Georg Cantor and Walter Christaller may have been aware of one another during their careers, however, there is no indication the two collaborated. Also, there is no documentation that Christaller’s central place theory (CPT) contains any tenets derived from Cantor’s middle third set (CMT). Regardless, CMT and CPT are linked by their constructions as nested hierarchies and the geometry of hexagons. The end points and intervals of CMT may be incorporated, respectively, as anchor points and radii for the hexagonal tessellations of central place theory.